Kombinasi Proses Filtrasi dan Ion Exchange Secara Kontinu pada Pembuatan Aquadm (Demineralized Water) - Reni Desmiarti (CHEMICA: Jurnal Teknik Kimia, 2017)
Demineralized water is water free of dissolved mineral. Combination of filtration and ion exchanger processes were studied to treat demineralized water. The source of raw water is from Mountain Talang in District Solok. The study was conducted to investigate the effect of the amount of resin cartridge to electric conductivity (EC), pH and total dissolved solid (TDS).Â  The flow rate was set at 50 ml/menit. The results showed that the number of resin cartridge 4 (2 anion and cation 2), the removal efficiency of EC and TDS achieved at 89.09% and 90.91%, respectively. As for the number of cartridges 6 (3 anions and cations 3), the removal efficiency of EC and TDS obtained at 95.45% and 96.36%, respectively.Â  In addition, the effect of flow rate was also studied using cartridges resin 6 (3 anions and cations 3). Demineralized water has met the quality standard with a value of 0 ppm TDS, EC 0 Î¼S / cm, pH 7.5. This studies shown that the combination of filtration and ion exchange filtration process can use effectively to treat demineralized water with high quality standard.